Phase transformations : examples from titanium and zirconium alloys - Banerjee, S. (Srikumar) (Pergamon materials series, 2007)
The terms phase transitions and phase transformations are often used in an interchangeable manner in the metallurgical literature. In this book, transformations driven by pressure changes, radiation and deformation and those occurring in nanoscale multilayers are brought to the fore. Order-disorder transformations, many of which constitute very good examples of continuous transformations, are dealt with in a comprehensive manner. Almost all types of phase transformations and reactions that are commonly encountered in inorganic materials are covered and the underlying thermodynamic, kinetic and crystallographic aspects elucidated. * Shows readers the advancements in the field - due to enhanced computing power and superior experimental capability * Drawing upon the background and the research experience of the authors, bringing together a wealth of experience * Written essentially from a physical metallurgists view point.